PRONet Duo insecticide-treated net incorporated with chlorfenapyr and bifenthrin is superior to Interceptor® G2 nets against pyrethroid-resistant Anopheles gambiae sensu lato: a randomized experimental hut trial in Côte d’Ivoire and Tanzania using non-inferiority design - Assenga, Alphonce A.; Ahoua Alou, Ludovic P.; Camara, Soromane; Koffi, Alphonsine A.; N’Guessan, Raphael; Kamande, Dismas S.; Ngonyani, Safina; Kibondo, Ummi A.; Odufuwa, Olukayode G.; Ntabaliba, Watson S.; Lekundayo, Ruth G.; Abilah, Faraji; et al. (Frontiers in Malaria, 2025)
BackgroundThe widespread development of pyrethroid-resistant Anopheles populations, has reduced the efficacy of pyrethroid insecticide-treated nets (ITNs), hindering malaria control efforts. This study tested PRONet Duo, a new ITN with two active ingredients-bifenthrin and chlorfenapyr. Bifenthrin is a fluorinated pyrethroid that is highly stable and more slowly detoxified by pyrethroid-resistant mosquitoes. Chlorfenapyr disrupts cellular energy production. The efficacy of PRONet Duo was compared to Interceptor® G2, an alpha-cypermethrin and chlorfenapyr ITN with proven efficacy in malaria reduction.MethodsThe study was conducted in two identical 9x9 Latin square experimental hut trials against wild free-flying Anopheles gambiae sensu lato in M’Bé, Côte d’Ivoire, and Lupiro, Tanzania using 18 experimental huts over 108 nights. The primary endpoint was the proportion of 72-hour mosquito mortality (M72) and the secondary endpoint was the proportion of mosquito blood-feeding. The study was done following World Health Organization guidelines. Data were analyzed using mixed-effect linear regression with a 7% margin of non-inferiority. Data were classified as non-inferior using delta and superior using the line of no difference.ResultsPRONet Duo demonstrated a non-inferior and superior mosquito mortality compared to Interceptor® G2 in both study sites. In Côte d’Ivoire, the M72 of PRONet Duo was 84% [81,88], higher than that of Interceptor® G2 (72% [68,76], OR: 1.54 [1.27,1.88]) and it was superior to MAGNet® (30% [27,34], OR: 13.74 [11.35,16.63], p<0.0001). In Tanzania, M72 of PRONet Duo was 68% [62,73], higher than that induced by Interceptor® G2 (44% [40,49], Odds Ratio (OR): 2.77 [2.31, 3.33]), and MAGNet® (36% [32,41], OR:4.82 [4.06,5.72] p<0.0001). PRONet Duo also induced non-inferior and superior prevention of blood-feeding compared to Interceptor® G2, with less than 11% feeding success observed in either trial site.ConclusionPRONet Duo ITNs are non-inferior and superior to the first-in-class Interceptor® G2 in terms of mosquito mortality and prevention of blood-feeding demonstrating the added benefit of bifenthrin for insecticide resistance management. Both chlorfenapyr nets offered superior mortality compared to the pyrethroid-only ITN. PRONet Duo offers an additional highly effective ITN for control of pyrethroid-resistant mosquitoes in malaria endemic regions.